Comparison between passive vision-based system and a wearable inertial-based system for estimating temporal gait parameters related to the GAITRite electronic walkway - González, Iván; López-Nava, Irvin H.; Fontecha, Jesús; Muñoz-Meléndez, Angélica; Pérez-SanPablo, Alberto I.; Quiñones-Urióstegui, Ivett (Journal of biomedical informatics, 2016)
[Display omitted] •Two low-cost systems for quantitative gait analysis are presented and compared.•The wearable inertial system relies on two acceleration sensors mounted on the ankles.•The vision system estimates gait events through 3D point-cloud processing.•Inter-group and intra-group analyses are provided over the two groups of adults.•Absolute/relative errors from gait parameters regarding the GAITRite are provided. Quantitative gait analysis allows clinicians to assess the inherent gait variability over time which is a functional marker to aid in the diagnosis of disabilities or diseases such as frailty, the onset of cognitive decline and neurodegenerative diseases, among others. However, despite the accuracy achieved by the current specialized systems there are constraints that limit quantitative gait analysis, for instance, the cost of the equipment, the limited access for many people and the lack of solutions to consistently monitor gait on a continuous basis. In this paper, two low-cost systems for quantitative gait analysis are presented, a wearable inertial system that relies on two wireless acceleration sensors mounted on the ankles; and a passive vision-based system that externally estimates the measurements through a structured light sensor and 3D point-cloud processing. Both systems are compared with a reference clinical instrument using an experimental protocol focused on the feasibility of estimating temporal gait parameters over two groups of healthy adults (five elders and five young subjects) under controlled conditions. The error of each system regarding the ground truth is computed. Inter-group and intra-group analyses are also conducted to transversely compare the performance between both technologies, and of these technologies with respect to the reference system. The comparison under controlled conditions is required as a previous stage towards the adaptation of both solutions to be incorporated into Ambient Assisted Living environments and to provide continuous in-home gait monitoring as part of the future work.